Hubungan Pengetahuan, Sikap, dan Pendidikan Ibu terhadap Pemenuhan Gizi Balita Usia 3-5 tahun di Kelurahan Lapulu - Juniarti, Riska; Demmalewa, Jenny Qlifianti; Ananda, Siti Hadrayanti (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2024)
The causes of malnutrition are divided into two, namely direct and indirect causes, namely children's food, an unbalanced diet in terms of nutritional content, and infectious diseases that children may suffer from. Indirect causes include food security in the family, childcare patterns and health services and environmental health. The purpose of this study was to determine the relationship between knowledge, attitudes, and maternal education towards the fulfillment of nutrition for toddlers aged 3-5 years in Lapulu Village. The type of research used is quantitative with a cross-sectional study design involving a sample of 31 people. The results of the study indicate that there is a relationship between Mother's Knowledge towards Fulfillment of Nutrition for Toddlers Aged 3-5 years in Lapulu Village (ρ value = 0.003), there is a relationship between Mother's attitude towards Fulfillment of Nutrition for Toddlers Aged 3-5 years in Lapulu Village (ρ value = 0.024) and there is a relationship between Mother's education towards Fulfillment of Nutrition for Toddlers Aged 3-5 years in Lapulu Village (ρ value = 0.019). It is concluded that there is a relationship between Mother's Knowledge, attitude and education towards Fulfillment of Nutrition for Toddlers Aged 3-5 years